2006
DOI: 10.1111/j.1365-2125.2006.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofibrate increases paraoxonase activity in patients with metabolic syndrome

Abstract: Aims Diabetic dyslipidaemia with decreased high‐density lipoprotein‐cholesterol (HDL‐C) concentration plays a key role in enhanced atherosclerosis. The antioxidant effect of HDL is due to the influence of human paraoxonase 1 (PON1) and several authors have described decreased activity of this enzyme in Type 2 diabetics and subjects with metabolic syndrome. The goal of this study was to examine the effect of daily ciprofibrate on serum PON1 and lipoprotein concentrations in patients with metabolic syndrome. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Recent studies have shown that PON-1, a protective enzyme for LDL-C oxidation, is an important molecule in the pathogenesis of atherosclerosis (25). PON-1 has been studied in MetS and obesity in several studies in different study groups, and the results of these studies are conflicting (18,(26)(27)(28). Senti et al showed that PON activity is lower in MetS compared to controls, and they suggested that the increased oxidative stress is related with the low PON activity (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PON-1, a protective enzyme for LDL-C oxidation, is an important molecule in the pathogenesis of atherosclerosis (25). PON-1 has been studied in MetS and obesity in several studies in different study groups, and the results of these studies are conflicting (18,(26)(27)(28). Senti et al showed that PON activity is lower in MetS compared to controls, and they suggested that the increased oxidative stress is related with the low PON activity (18).…”
Section: Discussionmentioning
confidence: 99%
“…reported that ciprofibrate increased paraoxonase activity in patients with metabolic syndrome [26]. The enzymespecific effect of ciprofibrate on 3-hydroxy steroid dehydrogenase-isomerase (3-HSD) in the testes, a tissuespecific effect, was also evident since no significant effects of ciprofibrate were reported in the activities of 3-HSD or Steroid 21-hydroxylase (21-OHase) in the adrenal glands of the same animals [27].…”
Section: Discussionmentioning
confidence: 84%
“…Numerous in vitro and in vivo studies have investigated the effect of ciprofibrate on enzyme activities [24][25][26][27]. Goll et al applied ciprofibrate and its species at varying concentrations (100-500 mM) to rat hepatocyte culture for 72 hours and reported an increase in the activities of mitochondrial enzymes (acyl CoA oxidase (ACO) and carnitine acetyl transferase (CAT)) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal studies support the clinical evidence of the stimulatory effects of lipid-lowering activity of drug therapy [22]. Fibrate group of drugs gemfibrozil, fenofibrate and ciprofibrate ( Figure 1) were found to increase the serum PON activity [23][24][25][26]. In patients with coronary disease, lowdose aspirin increases ~ 13% of serum PON1 activity [27], but in healthy volunteers it was found not to increase the activity [28].…”
Section: Introductionmentioning
confidence: 71%